2006
DOI: 10.1159/000092953
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Pulmonary Rehabilitation in Severe and Disabled COPD Patients

Abstract: Background: The optimal frequency of delivering a pulmonary rehabilitation program (PR) is not yet a well established issue. It is still unclear whether repeated PR at established intervals will result in effective maintenance or further improvement in the patient’s health status. Objectives: To investigate whether more frequently repeated PR in patients with COPD (1) leads to similar short and long-term physiological gains, and (2) decreases the burden due to hospitalization. Methods: Thirty-five disabled COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 41 publications
2
45
1
Order By: Relevance
“…In line with this, 6-MWD in COPD is known to be valuable for clinical assessment, monitoring and prediction of survival [10,11,12,13,14,43,44,45]. Recent data even suggest that 6-MWD can indicate clinical changes not detectable in the sequential evaluation of pulmonary impairments alone [44].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In line with this, 6-MWD in COPD is known to be valuable for clinical assessment, monitoring and prediction of survival [10,11,12,13,14,43,44,45]. Recent data even suggest that 6-MWD can indicate clinical changes not detectable in the sequential evaluation of pulmonary impairments alone [44].…”
Section: Discussionmentioning
confidence: 93%
“…Most of the evidence favoring 6-MWD in the evaluation of treatment effects [9,10,11,12] and prediction of survival has been obtained in COPD [8, 13, 14], consistent with the fact that COPD exhibits multiple systemic manifestations beyond the respiratory impairment itself [14,15,16,17,18], e.g. reductions in body mass index (BMI) and fat-free mass [4, 18], which affect 6-MWD [19].…”
Section: Introductionmentioning
confidence: 99%
“…15 Similarly, in a previous 2-y controlled study, Foglio et al 40 showed that successive, annual interventions lead to similar short-term gains but do not result in additive long-term physiologic benefits, except for the further reduction in the number of exacerbations. On the other hand, some additional physiological and clinical benefits were observed by Romagnoli et al 41 in a study in which subjects repeated PR programs more frequently, that is, every 6 months. However, we did not observe a significant difference in EQ-VAS change between subjects with COPD that had undergone a single PR program Shown are the results of Pearson's correlation coefficient (r) when all subjects are considered.…”
Section: Discussionmentioning
confidence: 94%
“…[10][11][12][13][14][15][16]19,36,37 Nevertheless, we are unaware of reports of home-based pulmonary rehabilitation programs that have included only patients receiving long-term oxygen treatment. The majority of previous studies have excluded such patients [10][11][12]14,15,17,18 programs where vital signs may be better monitored during exercise and better results may be achieved, 15,38,39 the reality is that this is not always possible. As Boxall et al 19 suggest and as our data support, severe COPD sufferers are frequently those who have the most difficulty in accessing hospital programs.…”
Section: Discussionmentioning
confidence: 99%